Resistance to Fusarium causing rots in wheat: topicality and prospects for its use in Mexico - Suaste Franco, María del Pilar; Iturriaga de la Fuente, Gabriel; Solís Moya, Ernesto; Raya Pérez, Juan Carlos; Ramírez Pimentel, Juan Gabriel; Mariscal Amaro, Luis Antonio (Revista Mexicana de Ciencias Agrícolas, 2020)
Root rot, crown and stem rot in wheat are considered a serious threat to this cereal in various parts of the world since the losses that cause grain yield and quality reach up to 89% and can be comparable to those caused by rust, in addition to the fungi associated with these rotting synthesize mycotoxins that can contaminate food products. This problem in Mexico has been little studied; however, in recent years, these diseases in irrigation and temporary wheats have been more incidents which is causing concern in the producers of this cereal in the country. This review summarizes current aspects of the disease, the sources of resistance available worldwide, as well as how this resistance operates in the Fusarium-wheat patosystem. The genetic basis of resistance to root, stem and crown rot of hexaploid wheats has been examined; through the mapping of Quantitative Trait Loci (QTL). To date, 44 QTL have been identified on 14 chromosomes with alleles that induce resistance to this disease and that are derived from hexaploid wheats and close relatives. Genetic improvement for this disease through introgression of alleles with these QTL is the most feasible strategy and the pyramidation of these QTL seems to be the most viable strategy in genetic improvement programs. Important step for the management of the problem in the wheat producing areas in Mexico
Keywords: Triticum aestivum L.; genetics; QTL; wilting